2022
DOI: 10.1002/advs.202105958
|View full text |Cite
|
Sign up to set email alerts
|

Degenerated Hole Doping and Ultra‐Low Lattice Thermal Conductivity in Polycrystalline SnSe by Nonequilibrium Isovalent Te Substitution

Abstract: Tin mono-selenide (SnSe) exhibits the world record of thermoelectric conversion efficiency ZT in the single crystal form, but the performance of polycrystalline SnSe is restricted by low electronic conductivity (𝝈) and high thermal conductivity (𝜿), compared to those of the single crystal. Here an effective strategy to achieve high 𝝈 and low 𝜿 simultaneously is reported on p-type polycrystalline SnSe with isovalent Te ion substitution. The nonequilibrium Sn(Se 1−x Te x ) solid solution bulks with x up to 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Besides all the potentials of the single crystal SnSe as a thermoelectric material, polycrystalline SnSe is restricted in performance due to the high thermal conductivity and low electronic conductivity. Isovalent doping (Te-dopant) as an effective strategy was utilized by He et al [205] to simultaneously enhance the electrical conductivity and reduce thermal conductivity in p-type polycrystalline SnSe. Using a two-step synthesis method, a nonequilibrium bulk Sn(Se1-xTex) solid solution with x up to 0.4 at.% realized a multifold increase in the carrier density (Eq.…”
Section: Tin Chalcogenidesmentioning
confidence: 99%
“…Besides all the potentials of the single crystal SnSe as a thermoelectric material, polycrystalline SnSe is restricted in performance due to the high thermal conductivity and low electronic conductivity. Isovalent doping (Te-dopant) as an effective strategy was utilized by He et al [205] to simultaneously enhance the electrical conductivity and reduce thermal conductivity in p-type polycrystalline SnSe. Using a two-step synthesis method, a nonequilibrium bulk Sn(Se1-xTex) solid solution with x up to 0.4 at.% realized a multifold increase in the carrier density (Eq.…”
Section: Tin Chalcogenidesmentioning
confidence: 99%
“…The Se in the SnSe is substituted by Te with a larger ionic size than Se, forming weak Sn−Te bonds to spontaneously release Sn. 30 As a result, holes are generated to increase the electrical conduction. Te-doped SnSe has been reported, 30−32 and Se-doped SnTe has also been studied.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the case of SnSe, the substitution of Te or S for Se in SnSe is a realization of this situation. The Se in the SnSe is substituted by Te with a larger ionic size than Se, forming weak Sn–Te bonds to spontaneously release Sn . As a result, holes are generated to increase the electrical conduction.…”
Section: Introductionmentioning
confidence: 99%
“…However, we consider that the solubility limit can be increased at high temperatures because the entropy term has a greater contribution with increasing temperatures. We previously reported that the non-equilibrium synthesis by high-temperature solid-state reaction and subsequent rapid thermal quenching could expand the solubility limit of Pb in 2D-layered (Sn 1– x Pb x )Se bulk polycrystals for x = 0.2–0.5, ,, that of Sn in 3D cubic (Sn 1– x Pb x )Se bulks for x = 0.6–0.5, and that of Te in 2D-layered Sn­(Se 1– x Te x ) bulks for x = 0.2–0.4 . Additionally, non-equilibrium vapor phase thin film deposition stabilized the 3D cubic (Sn 1– x Ca x )Se with x = 0.4–0.8, which cannot be obtained through equilibrium synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that the non-equilibrium synthesis by hightemperature solid-state reaction and subsequent rapid thermal quenching could expand the solubility limit of Pb in 2Dlayered (Sn 1−x Pb x )Se bulk polycrystals for x = 0.2−0.5, 8,9,20 that of Sn in 3D cubic (Sn 1−x Pb x )Se bulks for x = 0.6−0.5, 9 and that of Te in 2D-layered Sn(Se 1−x Te x ) bulks for x = 0.2− 0.4. 21 Additionally, non-equilibrium vapor phase thin film deposition stabilized the 3D cubic (Sn 1−x Ca x )Se with x = 0.4− 0.8, which cannot be obtained through equilibrium synthesis. 22 Therefore, we consider that the solubility limit can be expanded in (Sn 1−x Pb x )S by freezing the high-temperature solid-solution phase to RT.…”
Section: Introductionmentioning
confidence: 99%